Estudo dos princípios de categorização na Biblioteconomia e Ciência da Informação: Ranganathan - entre a teoria clássica e a abordagem cognitiva contemporânea - Alessandra Rodrigues da Silva (2010)
Categorization the cognitive process of understanding the characteristics of objects by similarity or dissimilarity criteria constitutes on Librarianship and Information Science (LIS) as an intrinsic activity of knowledge recording organization, and represents the central theme of this work. On the theoretical level, for almost two thousand years, the categorical logic that is pointed as the most influential to LIS and the matrix work in various areas of knowledge is the classical theory of categorization devised by Aristotle. Some LIS scholars envision categorization aligned with the Indian librarian Shiyali Ramamrita Ranganathan (1892-1972) works, in particular the fundamental categories proposed by him, expressed through the PMEST (personality, matter, energy, space and time) acronym. In experimental literature, a trial appropriation on this derivation, and if it actually happened, cannot be observed. Thus, since the 1970s analysis in LIS are associated to the cognitive elements, designed in this work as categorical gesture. We aimed to investigate the possible relationship between classical and contemporary cognitive categorization theories observing categorization as a cognitive process, and to understand how the categorical gesture happens on the different categorization levels on LIS (classifier and classificationist), based on Ranganathans works. We started from exploratory research through an immersion in the subject of theoretical concepts of classification and categorization. We noticed that categorization is differently configured, depending on the portrayed period and also on the needing to recover LIS-oriented categories studies, once they are characterized as the subjects-environment relationship foundation. The categorical principles present in the classical theory, in PMEST structure, and on contemporary cognitive approach were discussed. On the empirical scope, we used verbal protocol on classificationists and classifiers, by performing a task in an information retrieval tool prepared under Ranganathan categorical principles the Tesauro de Folclore e Cultura Popular Brasileira [Thesaurus of Brazilian Popular Culture and Folklore TFCPB], followed by a semi structured interview. In the analysis of these subjects categorical gestures, we could notice that there are points that oscillate between the different categorical proposals, and also the occurrence of a certain weakening of the PMEST structure on the performed categorization, which contradicts the assumptions outlined through research. In this way, we believe that the evidence found in Ranganathans categorical cognitive principles alternate between the classical theory and the contemporary cognitive approach, mixed according to the type of the depicted categories facet, beyond the above mentioned PMEST structure weakening on the practical usage on LIS categorization.